Large Genomic Deletions in CACNA1A Cause Episodic Ataxia Type 2 - Wan, Jijun; Mamsa, Hafsa; Johnston, Janine L.; Spriggs, Elizabeth L.; Singer, Harvey S.; Zee, David S.; Al-Bayati, Alhamza R.; Baloh, Robert W.; Jen, Joanna C. (Frontiers in Neurology, 2011)
Episodic ataxia (EA) syndromes are heritable diseases characterized by dramatic episodes of imbalance and incoordination. Episodic ataxia type 2 (EA2), the most common and the best characterized subtype, is caused by mostly nonsense, splice site, small indel and sometimes missense mutations in CACNA1A. Direct sequencing of CACNA1A fails to identify mutations in some patients with EA2-like features, possibly due to incomplete interrogation of CACNA1A or defects in other EA genes not yet defined. Previous reports described genomic deletions between 4-40kb in EA2. In 47 subjects with EA (26 with EA2-like features) who tested negative for mutations in the known EA genes, we used Multiplex Ligation-dependent Probe Amplification (MLPA) to analyze CACNA1A for exonic copy number variations. Breakpoints were further defined by long-range PCR. We identified distinct multi-exonic deletions in three probands with classic EA2-like features: episodes of prolonged vertigo and ataxia triggered by stress and fatigue, interictal nystagmus, with onset during infancy or early childhood. The breakpoints in all three probands are located in Alu sequences, indicating errors in homologous recombination of Alu sequences as the underlying mechanism. The smallest deletion spanned exons 39 and 40, while the largest deletion spanned 200kb, missing all but the first three exons. One deletion involving exons 39 through 47 arose spontaneously. The search for mutations in CACNA1A appears most fruitful in EA patients with interictal nystagmus and onset early in life. The finding of large heterozygous deletions suggests haploinsufficiency as a possible pathomechanism of EA2.